Rational design of a material for rapid colorimetric Fe2 + detection. (5th October 2016) - Laschuk, Nadia O.; Ebralidze, Iraklii I.; Quaranta, Simone; T. W. Kerr, Stephen; Egan, Jacquelyn G.; Gillis, Scott; Gaspari, Franco; Latini, Alessandro; Zenkina, Olena V.
Abstract: We report on the rational design of a novel TiO2 based screen-printed material suitable for sensitive and selective detection of iron ions in water. This includes the synthesis and characterization of large mesoporous TiO2 nanostructures, screen-printing of thick titania films on glass surfaces and their functionalization with 2, 2′:6′, 2″-terpyridin-4′-ylphosphonic acid (terpy). The ultra-high affinity between iron ions and the TiO2 -anchored terpy receptor makes this system potentially applicable to the analysis of iron in environmental, food, biological, and biomedical systems by a readily quantifiable colour change. Rapid (< 30 s) colour change of the material from white to magenta permits easy detection of as low as 0.3 ppm of Fe 2 + by the naked eye. The intensity of the colour change depends on the nature of the nanoparticles, the overall TiO2 film thickness, and the Fe 2 + concentration. The material was characterized using profilometry, diffuse reflectance UV–vis spectroscopy, and X-ray photoelectron spectroscopy (XPS) before and after treatment with aqueous solutions of Fe 2 + . The designed material shows colour reversibility upon treatment with EDTA solutions, which allows for multiple reuses of the same film with no effect on sensitivity. Graphical abstract: Highlights: Deposition of terpy based ligand, L, on TiO2 support results in hybrid material able to selectively react with Fe 2 + . Impregnation of iron (II) into hybrid material leads to distinct colour change from white to magenta. A novel material based on screen-printed mesoporous TiO2 beads functionalized byL was designed and characterized. The material is able to quantify 0.3 to 5 ppm of Fe 2 + in aqueous solutions.